Preoperative Hemoglobin Level, Oxygen Saturation and Postoperative Outcomes in Children With Cyanotic Congenital Heart Disease: A Propensity-Score Matching Analysis - Zhou, Dan; Deng, Li-Jing; Ling, Yun-Fei; Tang, Meng-Lin (Frontiers in Pediatrics, 2022)
Background The optimal preoperative hemoglobin (Hb) level is difficult to define in children with cyanotic congenital heart disease (CHD) due to hypoxemia-induced secondary erythrocytosis. This retrospective study integrated preoperative Hb and pulse oxygen saturation (SpO2) using the product of Hb × SpO2 to predict postoperative outcomes in children with cyanotic CHD. Patients and Methods Children aged <18 years undergoing cardiac surgery with cyanotic CHD were included. The cutoff value of Hb × SpO2 was the age-adjusted lower limit of normal Hb (aaHb) in healthy children. The main outcomes were in-hospital death and the composite outcome of severe postoperative events. Multivariate logistic regression analysis and propensity score matching analysis were used to adjust for important confounders. Results The presence of preoperative Hb × SpO2 < aaHb was observed in 21.6% of cyanotic children (n = 777). Children with Hb × SpO2 < aaHb had higher in-hospital mortality (12.5% vs. 4.6%, P < 0.001) and composite outcome incidence (69.6% vs. 32.3%, P < 0.001) than those with Hb × SpO2 ≥ aaHb. After propensity score matching, 141 pairs of children were successfully matched. Multivariate analysis showed that preoperative Hb × SpO2 < aaHb was significantly associated with the composite outcome in the entire population (odds ratio = 4.092, 95% confidence interval = 2.748–6.095, P < 0.001) and the matched cohorts (odds ratio = 2.277, 95% confidence interval = 1.366–3.795, P = 0.002). Conclusion Our results suggest that a preoperative Hb × SpO2 value below the lower limit of normal hemoglobin is a prognostic factor in cyanotic children undergoing cardiac surgery and is a potential criterion to evaluate preoperative anemia in this population.